Rapidly IPv6 multimedia management schemes based LTE-A wireless networks - Abeer Twakol Khalil; A. I. Abdel-Fatah; Hesham Ali Sakr (Institute of Advanced Engineering and Science, 2019)
Ensuring the best quality of smart multimedia services becomes an essential goal for modern enterprises so there is always a need for effective IP mobility smart management schemes in order to fulfill the following two main functions: (I) interconnecting the moving terminals around the extended indoor smart services. In addition, (II) providing session continuity for instant data transfer in real-time and multimedia applications with negligible latency, efficient bandwidth utilization, and improved reliability. In this context, it found out that the Generalized Multi-Protocol Label Switching (GMPLS) over LTE-A network that offers many advanced services for large numbers of users with higher bandwidths, better spectrum efficiency, and lower latency. In GMPLS, there is an elimination of the routing searches and choice of routing protocols on every core LTE-A router also it provides the architecture simplicity and increases the scalability. A comparative assessment of three types of IPv6 mobility management schemes over the LTE-A provided by using various types of multimedia. By using OPNET Simulator 17.5, In accordance with these schemes, it was proven that the IPv6-GMPLS scheme is the best choice for the system's operation, in comparison to the IPv6-MPLS and Mobile IPv6 for all multimedia offerings and on the overall network performance.